Constellations, plants and Arab poetry in a Medieval Berber text - Brugnatelli, Vermondo (Kervan. International Journal of African and Asian Studies, 2023)
This paper discusses one paragraph of the Kitāb al-Barbariyya, a medieval Berber commentary on Abū Ġānim’s Mudawwana. The brief note examined is a comment on the answer to a legal question, which mentions the ancient Berber names of a constellation and of a plant, quoting two lines of Arabic poetry. The passage occupies seven lines (f. 126b, ll. 8-14) of the manuscript MS.ARA 1936 found at the Bibliothèque universitaire des langues et civilisations (BULAC) of Paris. The Berber words retrieved from this text are Amanar, the name of the constellation of Orion, and tabduɣt, the name of the cotton plant. Moreover, in this ancient text, the word (a)kermus, which in the contemporary Berber languages applies to some specific plants (figs, prickly pears, dates), and which, in this case, seems to mean simply ‘fruit’, which supports a possible etymology from the Greek karpós. A list of Arab authors quoted within the Kitāb al-Barbariyya is added at the end of the paper.
Number: 2
Keywords: Fiqh – Libye – 8e siècle; Linguistique

اختيارات الإمام الربيع في كتاب النكاح من خلال المدونة الكبرى لأبي غانم الخرساني - فرج, حاتم بن رشيد (2023)
النادي الثقافي
Keywords: Fiqh – Libye – 8e siècle

المنهج الفقهي والأصولي عند الإمام الربيع بن حبيب دراسة في كتاب المدونة الكبرى لأبي غانم الخراساني كتاب البيوع أنموذجا - تمزغين, يوسف بن علي (2023)
النادي الثقافي
Keywords: Fiqh – Libye – 8e siècle

التخريج الفقهي عند الإمام الربيع بن حبيب من خلال المدونة الكبرى لأبي غانم الخرساني - باباواسماعيل, زهير بن مسعود (2023)
النادي الثقافي
Keywords: Fiqh; Fiqh – Libye – 8e siècle

مرويات الإمام الربيع بن حبيب في مدونة أبي غانم الخرساني : دراسة استقرائية حديثة - السيابي, حاتم بن رشيد (2023)
النادي الثقافي
Keywords: Fiqh – Libye – 8e siècle